Phase 2 trial of monoamine oxidase inhibitor phenelzine in biochemical recurrent prostate cancer - Gross, Mitchell E.; Agus, David B.; Dorff, Tanya B.; Pinski, Jacek K.; Quinn, David I.; Castellanos, Olga; Gilmore, Patrick; Shih, Jean C. (Prostate cancer and prostatic diseases, 2021)
Purpose Monoamine oxidase A (MAOA) influences prostate cancer growth and metastasis in pre-clinical models. We examined effects of phenelzine (a monoamine oxidase inhibitor) in patients with biochemical recurrent castrate-sensitive prostate cancer. Materials and methods An open-label single arm clinical trial enrolled subjects with biochemical recurrent prostate cancer defined by PSA ≥ 0.4 ng/ml (post prostatectomy) or PSA ≥ 2 ng/ml above nadir (post-radiation therapy); no evidence of metastasis on imaging; and normal androgen levels. Subjects received phenelzine 30 mg orally twice daily. Mood symptoms were assessed with the hospital anxiety depression score (HADS) questionnaire. The primary endpoint was the proportion of patients who achieved a PSA decline of ≥50% from baseline. Results Characteristics of the 20 eligible patients enrolled included: mean ± SD age 66.9 ± 4.8 years and PSA 4.7 ± 5.8 ng/dl. Maximal PSA declines ≥30% and ≥50% were observed in 25% ( n = 5/20) and 10% ( n = 2/20) of subjects, respectively. At 12 weeks, 17 subjects remained on treatment with PSA declines ≥30% and ≥50% of 24% ( n = 4/17) and 6% ( n = 1/17), respectively. Common toxicities observed included dizziness (grade 1 = 45%, grade 2 = 35%), hypertension (grade ≥ 2 = 30%), and edema (grade 1 = 25%, grade 2 = 10%). There was one episode of grade 4 hypertension (cycle 4) and two episodes of grade 3 syncope (cycle 12 and cycle 14) requiring treatment discontinuation. HADS questionnaires demonstrated a significant decrease in anxiety with no change in depressive symptoms on treatment. Conclusions Phenelzine demonstrated efficacy in patients with biochemical recurrent castrate-sensitive prostate cancer. Most treatment-related toxicities were mild, but rare significant and reversible cardiovascular toxicities were observed. Therapies directed at MAOA may represent a new avenue for treatment in patients with recurrent prostate cancer.